Growing Developing Talents and Increasing Self-Confidence in Children at TPQ An-Nuriyah through Mc and Dai Training - Arif Rifa’i; Ahmad Najmudin; Riki Radinata; Khoiru Rohmah; Suryani Dwi Rahayu; Siti Maimunah; Ike Saputri; Bella Alfifah; Hernisawati (International Journal of Community Engagement Payungi, 2024)
Taman Pendidikan Al-Quran (TPQ) is an Islamic non-formal education institution which aims to teach reading the Koran and the basics of religion to young children. The students at TPQ An Nuriyah are very active and show positive energy, so their memorization skills and self-confidence need to be improved. Lack of proper channels to channel their positive energy, which can lead to less productive behavior. In an effort to overcome this problem and develop talents and increase children's self-confidence, Master of Ceremony (Mc) and Dai training is considered an effective way. Mc trains public speaking and mental skills, while Dai delivers  skills to convey goodness and understand Islamic teachings. It is hoped that this training can help TPQ An Nuriyah children become more confident, develop abilities and build better character. In In this assistance, we use the "Service-Learning Approach" (SLA) method. This approach is an approach that attempts to fulfill the practical needs of the assisted community through practical learning or training activities. The result showed that this assistance ;mc and dai training can develop talents and train the students' self-confidence and increase their character to be even better. Keywords:  Developing Talents, Increasing Self-Confidence, Mc and Dai Training